Mechanical properties of concrete containing 15% and 20% of textile wastewater - Muhamad Aizat, Lengah (2010)
Textile industry is one of the most important and rapidly developing industrial sectors in Malaysia.It has a high effect in terms of its environmental impact in producing highly polluted discharge water in large amounts.Textile mills in Malaysia are required to control their discharge and therefore have started installing treatment plants in the name of environmental protection.Besides that,concrete are the most widely used man-made construction material and playing important part in all building.It can be defined as a composite material composed of a coarse granular material embedded in a hard matrix of material(cement or binder)that fills the space between the particles and bond together.Many researchers have been done to produce concrete which is economic as possible.The environmental regulation have initiated in increasing interest in using wastewater as a construction materials partially replacing the tap water in concrete structures.In this study,the idea is replacing tap water with textile wastewater(WWC)as concrete material.The objective of this study concentrates on mechanical properties that are compressive and flexural strength of concrete with WWC.There are two different percentages of WWC which is 15% and 20% were used to replaced the tap water and were tested at 7 and 28 days.The strength of normal concrete as a control mix has been compared with the concrete with WWC.The result revealed that the normal concrete presented the highest compressive and flexural strength and the followed by concrete with 15% and 20% WWC but have the potential to increase from 15% to 20% WWC.As a conclusion, WWC will increases the compressive and flexural strength of concrete but still need suitable percentage to be targeted for concrete used in construction.